Schwarzschild and de Sitter solutions from the argument by Lenz and Sommerfeld - Cuzinatto, R. R.; Pimentel, B. M. [UNESP]; Pompeia, P. J. (Amer Assoc Physics Teachers Amer Inst Physics, 2011)
The Lenz-Sommerfeld argument allows an ingenious and simple derivation of the Schwarzschild solution of Einstein equations of general relativity. We use the same reasoning to construct the de Sitter line element. (C) 2011 American Association of Physics Teachers. [DOI: 10.1119/1.3557070]